Effect of nitrogen on seed yield and content and quality of oil of winter grown sunflower (Helianthus annuus L.) - Daffalla, Ahmed E.; Lazim, M.E.; Farah, S.M.; Ahmed, E.A. (Gezira Journal of Agricultural Science, 2013)
ABSTRACT     Field trials were carried out at Wad Medani and Sennar locations during season 2008 / 09 to investigate the effects of nitrogen levels on growth, seed yield, oil content and quality of two sunflower cultivars. The treatments consisted of three nitrogen levels (86.7, 108 and 129 kg N/ha, applied as urea) and two cultivars (Damazin and Hysun33). Nitrogen at the higher rate (129 kg N/ha) gave higher seed yield. The oil content ranged from 36.3 to 42.9 %. Nitrogen, cultivar and location had no significant effects on oil content. Oleic and linoleic acids were the most dominant fatty acids in the oil. It is recommended to apply 129 kg N/ha to winter grown sunflower to obtain high seed yield.